African Perspectives of Research in Teaching & Learning (APORTAL) Vol 7 (2) (2023) - Wadesango, Newman editor in chief (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
Refer to the document
APORTAL completed issue
Keywords: Communication skills; COVID-19; Experiences; Higher education; Service- learning; Transformative; Behaviour management theory; Cyberbullying; Narrative enquiry; Social media; Teacher workload; Challenges; Possibilities; Teaching methods; Learner-centered; Teacher- centered; Culture of peace; Learners; Peace buddies; Peace education; School violence; South Africa; Curriculum and assessment policy; Ethnicity; Language policy; Minority group; Translanguaging; Inclusive education; Feminist pedagogy; Gender; Auto- ethnography; Higher education; ODeL; Open distance education; Electronic learning; E-learning system; Higher learning institutions; Diaspora; Orphan; Emigration; Learners left behind; Ideological; Consistency; Defense; Contradictions; Decolonization; New academics; Online teaching and learning; University teachers; Needs analysis questionnaire; Face-to-face teaching; School leadership; High performing contexts; Student Performance; Instructional leadership; Distributive leadership; Pedagogical leadership; Algebra; Algebraic expressions; Algebraic language; Content coverage; Factorisation; Opportunity to learn; Facebook; Knowledge; Development; Education -- Study and teaching; Education, Higher; Social media in education; Cyberbullying; COVID-19 (Disease); Translanguaging (Linguistics); Leadership; School management teams; Algebra -- Study and teaching (Secondary); Pedagogy; Curriculum-based assessment; Academic achievement; Mathematics -- Study and teaching; Blended learning; College students